The Impact of Effective Digital Onboarding on the Growth of Islamic Bank Customers in Indonesia - Muhammad Arif; Laylan Syafina; Salwa Latipah (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the relationship between the effectiveness of digital onboarding and the acceptance of digital banking services at Bank Syariah Indonesia in Medan. Research Method: This study employs an associative quantitative approach with a cross-sectional design. Data were collected through a questionnaire distributed to 100 respondents who had used the digital onboarding service at Bank Syariah Indonesia in Medan. Data analysis was conducted using simple linear regression in SPSS, supported by tests of validity, reliability, normality, and heteroscedasticity. Results and Discussion: The study indicates that digital onboarding has a positive and significant relationship with the acceptance of digital banking services. Ease of registration, time efficiency, flexibility of access, and ease of use of the system shape the public’s positive perception of digital banking services. These findings support the Technology Acceptance Model (TAM) and the Diffusion of Innovations Theory. Implications: This study offers practical guidance for Islamic banking institutions on improving the quality of digital onboarding services to enhance public acceptance of digital services and advance financial inclusion. Originality: This study focuses on digital onboarding as an initial mechanism for adopting digital services in Islamic banking in Medan